Improving entrepreneurial competencies in the classroom: An extension and in-study replication - Caroline E. W. Glackin; Steven E. Phelan (New England Journal of Entrepreneurship (NEJE), 2020)
Purpose - A recent paper by Morris et al. (2013b) presented evidence that students can develop entrepreneurial competencies through international fieldwork. This paper explores whether the same results can be developed in a traditional classroom setting. Design/methodology/approach - The study is a systematic replication of the Morris study with the addition of a matched pair, quasi-experimental design, with a self-replication. Data were collected on 13 self-reported competencies at the start of a semester from two groups using the Morris instrument. The treatment group was exposed to a curriculum designed to teach entrepreneurial competencies, and both groups were re-surveyed at the end of the semester. The process was then repeated with a different cohort, one year later, to replicate the initial study. Findings - Five competencies saw significant increases in the first treatment group. However, only three of these competencies increased more in the treatment group than the control group. In the replication study, only one competency was significantly higher in the treatment group, and that competency was not one of the original three. Practical implications - Educators and policymakers should select a curriculum that is valid and reliable. Entrepreneurship educators and policymaker should devote more time to evaluating the effectiveness of different pedagogical techniques for improving entrepreneurial competencies. Originality/value - To the best of our knowledge, this is one of the first studies in entrepreneurship education to undertake a matched pair, quasi-experimental design with an in-study replication. The results indicate that serious inferential errors arise if simpler designs are used, even though such designs are the norm in entrepreneurship research.
Keywords: 650; Entrepreneurial competencies; Entrepreneurship education; Measurement